Benzothiadiazole-based bolaamphiphiles: synthesis, self-assembly and white-light emissive properties. Issue 5 (11th January 2019) - Xiao, Yulong; Zhang, Ruilin; Gao, Hongfei; Zhao, Hongmei; Cheng, Xiaohong
Abstract : The first BTD-based D–A–D bolaamphiphiles featuring double walled square honeycomb LC phases, red fluorescent gels and white light emissive properties have been reported. Abstract : Novel benzothiadiazole-based bolaamphiphiles comprising a donor–acceptor–donor (thiophene–benzothiadiazole–thiophene) π-conjugated rod, two diol groups at the terminals and two alkyl chains at the lateral positions can self-assemble into square honeycomb LC phases and helical gel structures in organic solvents. The square columnar phases should have 4 molecules in each unit cell and 2 molecules in each cell wall with the c -parameter (intermolecular distance) varying from compound to compound. The UV-vis spectra of these red emissive BTD-based bolaamphiphiles covered almost the whole visible range with a relatively low band gap. Most interestingly, white light with CIE coordinates (0.30, 0.33) was obtained by doping this BTD-based bolaamphiphile with a blue emissive dithiophene bolaamphiphile and yellow-green emissive tetrathiophene bolaamphiphile.